Pengembangan Biosensor Berbasis Plastik Zona Mikro untuk Skrining Aktivitas Antidiabetes pada Ekstrak Tanaman Obat - Indri Firma Wati; Bambang Kuswandi; Dwi Koko Pratoko (Pustaka Kesehatan, 2021)
Research on the diabetes mellitus (DM) treatment has recently been carried out, especially on discovering antidiabetic agents derived from plants. This study aims to determine the fabrication of microzone plastic-based biosensors, determine the optimal sensor conditions, analysis characteristics, and compare the biosensor with the UV-Vis spectrophotometric method. The results showed that the response time was 15 minutes, the linear range was 500-40000 µg / mL (R = 0.9989). The limit of detection (LOD) was 1109.6 µg / mL, and the limit of quantification (LOQ) was 3698.8 µg / mL. Biosensor filled up the precision parameters with an RSD value of less than 3.7% and an accuracy with recovery in the range of 95-105%. The biosensor is stable in storage at 25 ° C for 270 minutes and at chiller temperature for three days. The antidiabetic activity of the biosensor was compared with the UV-Vis spectrophotometer using the Independent Sample T-test and showed insignificant differences between the two methods.